National institutions for the protection of the interests of future generations - Szabó,Marcel (2015)
Drawing from the persistent challenges related to sustainable development, the Rio+20 Summit invited the Secretary General of the United Nations to provide a report on the need for promoting intergenerational solidarity for the achievement of sustainable development, taking into account the needs of future generations. The Secretary General released his Report entitled “Intergenerational Solidarity and the Needs of Future Generations” in 2013, in which he established that intergenerational solidarity is embedded in the concept of sustainable development, and is a universal value of humanity. The Report named eight national institutions that have launched effective programs for the representation and protection of the needs of future generations and can serve as models for the further promotion of intergenerational solidarity. Furthermore, the Secretary General invited the UN High Level Political Forum to consider the most suitable mechanisms to promote intergenerational equity and sustainable development at the UN level. The present article seeks to explore the diverse solutions presented in the Secretary General's Report for the institutional protection of the human and natural environment, with the aim to delineate options for possible models to institutionalise concern for future generations at the national level, as well as to suggest options towards international cooperation to foster intergenerational equity and sustainable development at the regional and the global level.